The CTO as line manager - Gwynne, Peter
Peter Gwynne reports that CTOs with P&L responsibility believe they are more effective at improving their company's technology (and their own careers).
At a time when many American firms are deemphasizing the role of the chief technology officer; those CTOs who also have P&L responsibility explain the advantages-for their companies and themselves.
Chief technology officers, who aim to deliver the value of technology for their companies, bear one particularly difficult burden : The often lack credibility in a management culture focused on the bottom line. Some companies have set out to remedy that by adding a line job to the normal duties of their CTOs. They reason that the profit and loss responsibility that accompanies the line job will earn the CTO credibility with both top management and business units, and hence make the company more open to the CTO's technology agenda. Based on the experience of half a dozen CTO/line managers, the conceit works effectively : As the individuals gain an insider's view of the commercial pressures that face the company, they become more effective at improving their company's technology. The dual role can even help the company by narrowing the differences between long and short term planning.
Keywords: Line manager